The Influence Of Curriculum Management And Student Achievement In Enhancing Quality Education In The Era Of Digital Transformation - Muhamad Akpan Pauzi; Emaliana Gustiani; Zaera Khuswatun Khasanah; Nisak Ruwah Ibnatur Husnul (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
The digital transformation in education demands a strategic synergy between curriculum management and the enhancement of student achievement to ensure sustainable education quality. This study aims to analyze the synergy between curriculum management and student achievement in promoting quality education in the digital transformation era, using MI Nurul Falah Ciater as a case study. The research employed an associative quantitative approach. The subjects of the study were teachers, while the objects included curriculum management, student achievement, and education quality. The population consisted of 56 teachers, with a sample of 31 teachers selected through random sampling. The data collection technique was carried out through the distribution of questionnaires using a Likert scale. The data analysis utilized descriptive statistics and multiple linear regression, with instrument quality tested through validity and reliability tests, and classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. The results of the study indicate that: (1) partially, there is a significant effect of curriculum management on the quality of education, as evidenced by a t-value of 2.742 > 2.048 and a significance value of 0.011 < 0.05; (2) partially, there is a significant effect of learning achievement on the quality of education, as evidenced by a t-value of 3.550 > 2.048 and a significance value of 0.001 < 0.05; and (3) simultaneously, there is a significant effect of curriculum management and student achievement on the quality of education, as evidenced by an F-value of 33.521 > 3.34 and a significance value of 0.001 < 0.05. Based on these findings, it is recommended that primary education institutions such as MI Nurul Falah Ciater strengthen the coordination and implementation of adaptive curricula and develop integrated strategies to enhance student achievement through the utilization of digital technology.